Practicing sustainability in PFI project management - Nannan Wang; Ronggui Ding; Radosavljevic, M.; Hua Sun (2011 IEEE International Technology Management Conference, 2011)
This paper investigates the relationship of the project management in Private Finance Initiative (PFI) and sustainability. A live PFI project is selected as a case study, where contract review and monitoring on project management are carried out to evaluate the sustainability of project management. The PFI procurement shows great advantages in increased contractual responsibilities of the contractor in sustainable construction, and also in practicing sustainability in project management. Six main sustainable attributes of the project management are selected to evaluate the sustainability of project management in the PFI project. The project management process in the case study is closely monitored in order to verify how the PFI project promotes sustainability in practice. The project management in the different stages of the PFI project, including tendering, design, construction and operation, contributes to the six sustainable attributes in different ways. The project management in PFI project paid more attention in sustainable development during its whole process. As the private sector is responsible to the whole life of the building project, the project manager has to consider the long-term benefits during the management process. The government should take advantages of PFI project management in practicing sustainability therefore to promote sustainable development of the national infrastructure services.